If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6g+1=37
We simplify the equation to the form, which is simple to understand
6g+1=37
We move all terms containing g to the left and all other terms to the right.
+6g=+37-1
We simplify left and right side of the equation.
+6g=+36
We divide both sides of the equation by 6 to get g.
g=6
| 4x-4=4x-7 | | 1/3×3.14×25×9 | | 135/32 | | (3x+1)+3(3x+1)-5=875 | | 68+x+x=180 | | 32/135 | | -7(5+2x)=-49 | | 23+129+x=180 | | 4*ln(7x)=8 | | 2z^2-5z+4=0 | | 500x-13=65x-78 | | 6(-4x+7)-12=-7(2x+7) | | b^3+27= | | m^2x^3+m^9x^2+m^3x^4+m^6= | | 5(7+4x)=155 | | y^2+5y=7 | | 4x+3=9x+33 | | -3x+68-7(x-1)=8x-(2x-2)-6x+3 | | 1.05x=9.020 | | 2n+11=17 | | 3x+39=-69+12x | | -7x+18-7(x-3)=4x-(6x-6)8x+9 | | x^2+10c-25=0 | | 16x+2=8x+6 | | 3b^2+3b-6=0 | | n/3-7=5 | | x/5=181 | | 8/5(-3) | | 3b^2+3b+6=0 | | -[3x-(12x+5)]=5+(8x+6) | | r^2-4r=16+2r | | 8x-29=6x-7 |